Metal Industries in Basra Governorate: Ibn Majid Company as a Model - الرمضان, سندس احمد عبد القادر (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The company Ibn Majid. specialized in manufacturing heavy engineering equipment to meet the requirements of companies in the various sectors of oil, electricity and industrial.It also specializes in manufacturing marine ships, bridges and iron sections.In addition to possessing all the human potential and technical expertise necessary to carry out various works. as well as a study of the factories the company owns.The number of workers in Al Salam factory reached (182) workers and the design capacity reached (3045) tons, while the design capacity in the heat exchangers factory amounted to (3345) tons, with (131) workers,.As for Al-Wafaa factory its design capacity reached (2265) tons and the number of workers reached (108) workers , and finally Al-Nasr factory, which had the smallest number of workers where the workforce is (44) workers, including (18) workers who work for daily wages, and the production capacity reached (2300) tons. The most prominent problems and obstacles to which the company was exposed were also studied.